The Effect of Psychological Capital on Innovation in Information Technology - Babak Ziyae; Mohammad Hassan Mobaraki; Mozhgan Saeediyoun (Journal of Global Entrepreneurship Research, 2015)
In today's competitive world, innovation is considered as a key factor to success and survival for organizations. So far, the literature has recognized various items that affect innovation in organizations. This paper seeks to investigate the effect of psychological capital on innovation in Information Technology (IT) among branches of Agriculture bank in Tehran, Iran. In terms of objective, this study is considered as an empirical one, and the research methodology is descriptive-correlative type. The population includes 132 managers and employees working in Agriculture bank branches in Tehran. Among those people, 100 individuals were selected to be studied based on using Cochran formula and through random sampling method. Structural Equation Modeling (SEM) was used for data analysis. The Results of study showed a significant effect of psychological capital on innovation in IT. In addition, more specific analysis on each of the psychological capital dimensions (self-efficacy, hope, optimism, resilience) revealed that except resilience, none of them enhanced innovation in IT. Finally, this study proposes insights for managers how to enhance their employees' capabilities and psychological capital through constant measurement as well as using improvement plans in order to provide higher innovation in IT. The current research also provides more suggestion for future studies that could consider consequences of innovation in IT.
Keywords: 650; Psychological capital; Self-efficacy; Hope; Optimism; Resilience; Innovation